Quality of Elderly\'s Life in Tehran Senile Culture House Clubs - Mahnaz Ahangari (Sālmand, 2007)
Objectives: Today, the rate of aged persons in the world population is rapidly rising. For making decision and planning for this proups, we must know their problems exactly. One way for this purpose is to measure quality of life that it is one of the best criteria in the rehabilitation and health assessment. The objective of this study was to assess, quality of life and the some factors that affect such measures.